The Profile of Ocular Fibrous Histiocytoma Tumors at Dr. M. Djamil General Hospital, Padang, Indonesia - Eka Alpasra; Ardizal Rahman; Mardijas Efendi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Ocular fibrous histiocytoma tumors originate from histiocytic cells or primitive mesenchymal cells. A fibrous histiocytoma is basically composed of a mixture of fibroblastic cells, histiocytes, blood vessels, and collagen in various proportions. This study aimed to determine the profile of ocular fibrous histiocytoma tumors at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This study was a descriptive observational study. A total of 8 research subjects participated in this study. Data analysis was carried out with the help of SPSS version 24 software, and univariate analysis was carried out. Results: The majority of subjects were female, with an age range of 41-60 years. The clinical symptoms felt by patients are the presence of a mass. The majority of study subjects had disease onset < 6 months, and tumor sizes were 1-5 cm. The majority of tumor locations are on the eyelid, and the histopathologic overview shows xanthelasma and dermatofibromas. Excision therapy is the therapy for the majority of research subjects. Conclusion: Most types of fibrous histiocytoma tumors at Dr. M. Djamil General Hospital, Padang, Indonesia, are benign type and locally aggressive.